2015
DOI: 10.5539/jas.v7n6p69
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response to Different Irradiation Regimes during Barley Seedlings Growth Followed by Drought Stress under Non-Photoinhibitory Light

Abstract: Differences in physiological response of barley seedlings cultivated under low (LI, ~65 μmol m -2 s -1 ) and elevated irradiation (EI, ~450 μmol m -2 s -1 ) to upcoming drought were evaluated. After ten days of cultivation, drought stress was induced under LI by withholding water and was defined as: mild stress (MS), severe stress (SS), extreme stress (ES) and control (C, well watered). Decreased relative water content (RWC) in both LI and EI grown plants was associated with increased lipid peroxidation (TBARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Other researchers have confirmed the influence of added water on the ChlF, RWC [ 27 ], and GPOX [ 39 ], which was not the case in this study (except for PI ABS in 2013 and TR 0 /ABS in 2014). There was no statistically significant impact of irrigation, most probably because the amount of water was insufficient to make a difference.…”
Section: Discussionsupporting
confidence: 49%
“…Other researchers have confirmed the influence of added water on the ChlF, RWC [ 27 ], and GPOX [ 39 ], which was not the case in this study (except for PI ABS in 2013 and TR 0 /ABS in 2014). There was no statistically significant impact of irrigation, most probably because the amount of water was insufficient to make a difference.…”
Section: Discussionsupporting
confidence: 49%
“…Two frequently used photosynthetic parameters that serve as stress indicators in plants are the maximum quantum yield of PS II (F v /F m ) and the performance index (PI ABS ), both determined by measuring chlorophyll a fluorescence that originates almost exclusively from PS II. As revealed by previous investigations, the F v /F m parameter was not affected until severe drought stress occurred, while the PI ABS appeared to be much more sensitive to drought stress [ 18 , 19 , 20 ]. This corresponded to our results shown in Table 1 .…”
Section: Discussionmentioning
confidence: 78%
“…When compared between plants grown under different conditions, plants of BT and BF grown under lower light showed a higher content of these pigments relatively to those of UT and UF grown under higher light (Figure S2; Figure 6), indicating that light intensity is more important than the growth temperature in the production of photosynthetic pigments. An earlier work done by Lichtenthaler and Burkart (1999) showed that plants grown under high light had lower amount of chlorophylls per chloroplast, high chlorophyll a/b ratio, and high CO 2 assimilation rate. They also reported that the production of chloroplast starch was greatly increased in the plants grown under sunlight as compared with those grown under shading.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, UT plants recorded higher values of NPQ, qP, and R Fd than UF, BT, and BF plants (Figure 2), indicating that they had higher potential of performing photosynthesis. ChlF kinetic parameters of NPQ, qP, and R Fd are also useful in measuring plant stresses under adverse environmental conditions (Lichtenthaler and Miehé, 1997; Lichtenthaler and Burkart, 1999; Zivcak et al, 2014). In consistent with the observation that R Fd is an indicator correlating with the photosynthetic activity of whole leaves (Lichtenthaler et al, 2005).…”
Section: Discussionmentioning
confidence: 99%